Review Article MEDICAL WASTE MANAGEMENT AND MINIMIZATION - Mohapatra, Er.shuvendu Shekhar; Mishra, Akansha; Dash, Anshurekha (Innovare Journal of Medical Sciences, 2017)
Abstract: We all know that medical wastes are more hazardous than the municipal solid waste and household waste. The medical wastes are the unwanted and discarded materials that are commonly used day by day. Various types of disease-causing agents called as pathogens are found in a high amount of medical wastes. Some commonly caused diseases are parasitic infections, infections of the airways and lungs, meningitis, disease from improperly disposed of with traces of vaccines, bacteremia, infections of reproductive organs, sexually transmitted infections, HIV, hepatitis B and C viruses, and hemorrhagic fevers, and many other diseases. The various wastes generated from the healthcare sectors are needed to be minimized and managed in a safe way. The medical wastes are having a high public risk as it affects the normal environment. The medical wastes are the key factors for environmental pollution. Now a day the medical waste management has become a great challenge and having a critical issue as it is affecting the connected population as well as the environment. The main problem with the unsuccessful waste management can be due to the untrained employees (not known about the waste management) in the healthcare units. Awareness among the health workers for proper medical waste management should be there to create control over the successful minimization the medical waste and its hazardous effect on the public. So the medical waste management, as well as the minimization, is most necessary. This systematic study refers to a brief report on the medical wastes and the possible processes to making the society safe and beware of the hazardous wastes and their management by which the environmental pollution, as well as the public risk, could be reduced.